2017
DOI: 10.1002/jcb.25681
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Adipogenesis Through Differential Modulation of ROS and Kinase Signaling Pathways by 3,4′‐Dihydroxyflavone Treatment

Abstract: Studies on adipogenesis may be important for regulating human and/or animal obesity, which causes several complications such as, type II diabetes, hypertension, and cardiovascular disease, thus giving rise to increased economic burden in many countries. Previous reports revealed that various flavonoids have anti-apoptotic, antioxidant, and cell differentiation-regulating activities with a number of physiological benefits, including protection from cardiovascular disease, cancers, and oxidative stress. As we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Excess ROS can alter the activity of a particular enzyme by redox reaction, and participate in the regulation of autophagy and programmed cell death, and thus, exert adverse effects on the body[31]. We found that after B .…”
Section: Discussionmentioning
confidence: 99%
“…Excess ROS can alter the activity of a particular enzyme by redox reaction, and participate in the regulation of autophagy and programmed cell death, and thus, exert adverse effects on the body[31]. We found that after B .…”
Section: Discussionmentioning
confidence: 99%
“…The flavonoids 3-hydroxyflavone (3-HF), 3,2 -dihydroxyflavone (3,2 -DHF), 3,3 -DHF, and 3,4 -DHF enhanced the proliferation and differentiation of stem cells ( Figure 5A) [35,41,66]. Here, we also applied the flavonoids to examine their effect on the isolation efficiency and proliferation capacity of USCs on basic USC isolation protocol (gelatin group).…”
Section: Flavonoids Increase the Isolation Efficiency Of Uscsmentioning
confidence: 99%
“…As reported in earlier studies, MAPK and PI3K signaling pathways have roles in adipogenesis [2,22,23,24]. A previous study shows that ERK1/2 pathway only has a role at the early adipogenesis [1].…”
Section: Introductionmentioning
confidence: 73%